Divided, but not disconnected : German experiences of the Cold War ; [ ... symposium held in Liverpool in September 2006] - Hochscherf, Tobias 1976- Hrsg; Laucht, Christoph; Plowman, Andrew 1966- (Berghahn, 2010)
Divided, but not disconnected : Germany as a border region of the Cold War / Thomas Lindenberger -- Fighting the First World War in the Cold War : East and West German historiography on the origins of the First World War, 1949-1959 / Matthew Stibbe -- The sideways gaze : the Cold War and memory of the Nazi past, 1949-1970 / Bill Niven -- Recasting Luther's image : the 1983 commemoration of Martin Luther in the GDR / Jon Berndt Olsen -- West German labour internationalism and the Cold War / Quinn Slobodian -- The German question and Polish/East German relations, 1945-1962 / Sheldon Anderson -- From bulwark of freedom to cosmopolitan cocktails : the Cold War, mass tourism and the marketing West Berlin as a tourist destination / Michelle A. Standley -- Projections of history : East German film-makers and the Berlin Wall / Séan Allan -- Defending the border? : satirical treatments of the Bundeswehr after the 1960s / Andrew Plowman -- East versus West : Olympic sport as a German Cold War phenomenon / Christopher Young -- Films from the other side : the influence of the Cold War on West German feature film import in the GDR / Rosemary Stott -- The shadows of the past in Germany : visual representation, the male hero, and the Cold War / Inge Marszolek -- Reenacting the first battle of the Cold War : post-wall German television confronts the Berlin Airlift in Die Luftbrücke : nur der Himmel war frei / Tobias Hochscherf and Christoph Laucht -- Unusual censor readings : East German science fiction and the GDR ministry of culture / Patrick Major -- Funerals in Berlin : the geopolitical and cultural spaces of the Cold War / James Chapman